Participatory Boat Tracking Reveals Spatial Fishing Patterns in an Indonesian Artisanal Fishery - Navarrete Forero, Gabriela; Miñarro, Sara; Mildenberger, Tobias Karl; Breckwoldt, Annette; Sudirman,; Reuter, Hauke (Frontiers in Marine Science, 2017)
The Spermonde Archipelago holds one of the largest artisanal fisheries in Indonesia, providing livelihoods for local communities and many other people involved in international trade networks of seafood. High demand and a lack of enforcement of existing fisheries regulations turn into high pressure for the coral reef ecosystem, contributing to its overall degradation. Estimations on the ecological impacts of different levels of fishing pressure, as well as fisheries stock assessments and marine resource management require precise information of the spatial distribution of fishing effort, which involves great uncertainty when only anecdotal information is considered. We explored the feasibility of applying participatory boat tracking to complement fisheries data during the NW monsoon season 2014–2015. We conducted interviews, measured catch landings, and distributed GPS data loggers among hook and line fishermen to identify fishing grounds by gear-dependent patterns of boat movement. Most of the fishing activities involved two gears (octopus bait and trolling line for live groupers) and three fishing grounds. The mass of catch landings was dominated by Octopoda (CPUE = 10.1 kg boatday−1) while the most diverse group was the fish family Serranidae, with Plectropomus leopardus being the main target species. In conclusion, boat tracking combined with interviews and catch surveys has proven a useful tool to reduce uncertainty in information on spatial resource use, while allowing a high level of participation by fishermen.